Intraoperative Diagnosis of Sodium-Glucose Cotransporter 2 Inhibitor–Associated Euglycemic Diabetic Ketoacidosis: A Case Report. Issue 1 (January 2021) - Seger, Christian D.; Xing, Hanning; Wang, Libing; Shin, John S.
Abstract : The use of sodium-glucose cotransporter 2 (SGLT2) inhibitors is increasingly common in type 2 diabetes mellitus (DM) management. Patients taking an SGLT2 inhibitor are at risk for euglycemic diabetic ketoacidosis (EDKA). We report an intraoperative diagnosis of EDKA. The patient was found to have an arterial pH of 7.21 and serum beta-hydroxybutyrate of 88.8 mg/dL (normal: <3.0 mg/dL) with serum glucose <250 mg/dL. Acidosis resolved with insulin and glucose infusions. Perioperative specialists must recognize the potential for EDKA in patients taking SGLT2 inhibitors. Expert opinion suggests preoperative cessation for 2–3 days and intraoperative serum ketone concentration measurement for at-risk patients.